2012
DOI: 10.1002/dev.21091
|View full text |Cite
|
Sign up to set email alerts
|

Lateral manual asymmetries: A longitudinal study from birth to 24 months

Abstract: Longitudinal studies tracking the early development of manual asymmetries are fairly rare compared to the large number of studies assessing hand preference in infancy. Moreover, most prior longitudinal studies have performed behavioral observation over relatively short-time spans considering the celerity of early development. This study aims (i) to investigate the direction and consistency of manual lateral asymmetries over a longer period, from birth to 24 months of age, and (ii) to compare individual and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…7 In fact analysis of pre-reaching movements (head turning or post-startle preferences) in the first months of life show no correlation with future handedness. 9 The difficulty in assessment of the development of handedness is that periodic standard assessment of developmental milestones are not able to detect change and standard neurologic exams have a poor coorelation. 8 Overall, there is a human righthanded bias.…”
Section: 45mentioning
confidence: 99%
See 2 more Smart Citations
“…7 In fact analysis of pre-reaching movements (head turning or post-startle preferences) in the first months of life show no correlation with future handedness. 9 The difficulty in assessment of the development of handedness is that periodic standard assessment of developmental milestones are not able to detect change and standard neurologic exams have a poor coorelation. 8 Overall, there is a human righthanded bias.…”
Section: 45mentioning
confidence: 99%
“…10 With regular intensive evaluations, trajectories begin to lateralize from twelve to eighteen months. 9 Still, there is fluctuation of these trajectories based on a complex cascade of developmental contingencies. Bimanual manipulation requires acquiring objects with the non-dominate hand, then allowing the dominate hand to manipulate it.…”
Section: 45mentioning
confidence: 99%
See 1 more Smart Citation
“…That perceptual lateral bias has been proposed to be a potential factor inducing the predominant preference for the right hand to perform motor tasks in humans (Coryell & Michel, 1978;Michel, 1981;Michel & Harkins, 1986). Even though predominant side of head turning in the first months of life has been suggested to predict manual preference in older infants (Michel & Harkins, 1986), by the age of voluntary reaching onset manual preference is rather variable (Jacobsohn, Rodrigues, Vasconcelos, Corbetta, & Barreiros, 2014;Lynch, Lee, Bhat, & Galloway, 2008;Morange & Bloch, 1996;Ramsay, 1980;Rönnqvist & Domellöf, 2006;Seth, 1973;Souza, Azevedo Neto, Tudella, & Teixeira, 2012). Morange and Bloch (1996), for example, found predominance of left-handedness in 4-month-old infants, whereas Souza et al (2012) found approximately the same numbers of right-and left-handers in 5-month-olds.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In both cases, based on adult handedness population profile, featured by approximately 90% of right-handers (Brackenridge, 1981;Dahmen & Fagard, 2005), one can expect that a large part of those infants will shift their manual preference during the course of motor development. In fact, predominance of right hand preference has been shown to emerge during the second semester of life (Corbetta & Thelen, 1999;Fagard, Spelke, & von Hofsten, 2009;Michel, Tyler, Ferre, & Sheu, 2006;Morange & Bloch, 1996;Thelen, Corbetta, & Spencer, 1996), with evidence that infants' preference to grasp objects with the right hand increases until the end of the first year of life (Ferre, Babik, & Michel, 2010) or longer (Jacobsohn et al, 2014). From the findings reviewed thus far, it becomes apparent that if arms visibility plays a role in the development of manual preference that effect is expected to occur following the age of functional reaching onset rather than in the first months of life.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%